Расширенный метод выбора наблюдаемых переменных для мониторинга компьютерной сети - Саенко, В. И. (My University, 2013)
Розглядаються питання підвищення ефективності моніторингу шляхом зниження навантаження на комп'ютерну мережу службового трафіку. Запропоновані методологічні рішення для вибору достатнього числа контрольованих змінних. Метод використовує інтервальні оцінки значущості. Приклади розглядаються у рамках технології WMI. The questions on increase of monitoring efficiency by a deloading on the service traffic in computer network are considered. Methodological solutions of choosing observed variables for network monitoring are offered. The method uses the interval meaningful estimations. Experimental data are got within the WMI network monitoring technology.
Keywords: компьютерная сеть; мониторинг компьютерной сети; WMI; наблюдаемая переменная